Determinants in the use Pilipino by adults and children in Cebu City a sociolinguistic survey - Velasquez, Ester B. (Ester Balgue) 1944-
The aim of the study is to investigate the factors that help determine the use of Pilipino by adults and children in urban and rural barangays in Cebu City. It seeks to ascertain which factors are correlated with the Cebuanos' actual performance or proficiency in speaking and understanding Pilipino.